ANALYSIS OF THE RELATIONSHIP OF THE CONVECTIVE SYSTEM TO THE VALUE OF AREA REDUCTION FACTOR (ARF) - Haifa, Vivia
The Area Reduction Factor (ARF) is a correction value for regional rainfall to overcome the limitations of spatial rainfall data. ARF is used to convert the point average rainfall to the regional average rainfall. The Area Reduction Factor (ARF) value depends on the characteristics of rainfall in a watershed where the rain in an area is influenced by the convective system. In this study, the calculation of the Area Reduction Factor was carried out to determine the spatial rainfall in various areas of a certain area with a certain duration. The rainfall data used comes from the Global Precipitation Measurement (GPM) Final Precipitation satellite. The ARF calculation is divided into high PECS regions and low persistent elongated convective system (PECS) regions. The results showed that the PECS high region for a duration of ? 12 hours had a higher ARF value than the ARF value of other regions while for a duration of > 12 hours the ARF value for the PECS high region experienced a significant decrease as the area increased. Simplification was carried out to see the relationship between ARF and PECS and it was found that simplification of ARF for a wider area by following the steps of Saefulloh's (2020) research using the simplification equation of the ARF curve by Ginting (2010) obtained index A results which were similar to the ARF spatial plot as well as the value of the ARF curve. index a obtained from the Leclerc and Schaake (1972) equation, but the simplification using the Ginting (2010), Leclerc and Schaake (1972) equation was not able to identify the presence of PECS-type Mesoscale Convective System (MCS) based on the results of Firdaus (2019) research. So it can be concluded that ARF is not able to identify PECS type MCS properly.